Nanoscale Structure, Dynamics, and Aging Behavior of Metallic Glass Thin Films - Burgess, J. A. J. (Sci Rep, 2016)
Scanning tunnelling microscopy observations resolve the structure and dynamics of metallic glass Cu(100−x)Hf(x) films and demonstrate scanning tunnelling microscopy control of aging at a metallic glass surface. Surface clusters exhibit heterogeneous hopping dynamics. Low Hf concentration films feature an aged surface of larger, slower clusters. Argon ion-sputtering destroys the aged configuration, yielding a surface in constant fluctuation. Scanning tunnelling microscopy can locally restore the relaxed state, allowing for nanoscale lithographic definition of aged sections.